A cleaner and simple spectrophotometric micro-fluidic procedure for copper determination using nitroso-R salt as chromogenic agent - Kruanetr S. (2014)
A cleaner and simple spectrophotometric method using microflow analysis (μFA) was performed. It consisted of a T-junction with microcoil on a polymethyl methacrylate (PMMA) chip which was fabricated by laser ablation and a molded polydimethylsiloxane (PDMS) as top plate. The fabricated PMMA chip was integrated with light emitting diode (LED) as light source and spectrometer as detector. The proposed device was applied to determining copper in water samples using nitroso-R salt as chromogenic reagent at 495 nm. It was found that the proposed μFA system was with less reagents and samples consumption with tiny waste generation. The relative standard deviation (R.S.D.) was less than 2% (n = 11) with the percentage recovery of 98.0 ± 1.7% (n = 7). The linear range for determination of copper in water samples was over the range of 0.05-3.0 μg mL-1 with a correlation coefficient (r2) of 0.999. The limit of detection (3σ) was 47 ng mL-1 with a sample throughput of 30 h-1. © 2007 Elsevier B.V. All rights reserved.